DEEMPHASIZE COMMUNITY DEVELOPMENT PROGRAMS ON MIGRAN WORKERS - Chawa, Anif Fatma; Al Yusainy, Cleoputri; Adila, Isma; Kusumastuti, Ayu (Jurnal Terapan Abdimas, 2018)
Abstract.This study wants to address how migrant workers and their choices to work abroad have impacted its family, especially for economy and infrastructure sector. This paper explains that community development tend to adopt two approaches: micro or macro perspective. Macro perspective focuses on the people or agencies only in terms of their relationship to the large-scale structure, whilst micro-perspective places a greater emphasis on the individual level as the main focus and objective in the development programs. The objective of this research is to seize the structural issues of the migrant workers, and therefore, social mapping method is used. Social mapping is a visual method of showing the relative location of households and the distribution of different types of people (such as male, female, adult, child, landed, landless, literate, illiterate, and so on) together with the social structure and institutions of an area. This research was conducted in Sukowilangun village, near Malang, East Java, as this regency is named one of the largest migrant workers origins.Keywords: Migrant Workers, Indonesia, Social Mapping, Community Development  Abstrak. Penelitian ini ingin membahas bagaimana pekerja migran dan pilihan mereka untuk bekerja di luar negeri telah mempengaruhi keluarganya, terutama dalam sektor ekonomi dan infrastruktur. Makalah ini menjelaskan bahwa pengembangan masyarakat (community development) cenderung mengadopsi dua pendekatan perspektif yakni mikro atau makro. Perspektif makro hanya berfokus pada orang atau badan yang berkaitan dengan struktur yang berskala besar, sementara perspektif mikro lebih menekankan pada tingkat individu sebagai fokus utamanya dan program pembangunan sebagai objeknya. Tujuan dari penelitian ini adalah untuk menangkap isu struktural dari pekerja migran, penelitian ini menggunakan metode pemetaan sosial (social mapping). Social mapping adalah metode visual untuk menunjukkan lokasi relatif rumah tangga dan distribusi orang dari berbagai jenis (seperti laki-laki, perempuan, dewasa, anak-anak, rumah berubin atau tak berubin, terpelajar, buta huruf, dan lain-lain) bersama dengan struktur sosial dan institusi yang ada di area tersebut. Penelitian ini dilakukan di Desa Sukowilangun, Kabupaten Malang, Jawa Timur, karena kabupaten ini merupakan salah satu asal pekerja migran terbesar.Kata kunci: Buruh Migran, Indonesia, Pemetaan Sosial, Community Development